Special situation disposal and fault analysis of single engine parking for a certain type of helicopter - LIU Haoyang; SHI Lijun; XU Yunshan; WANG Zhirui; CAI Yingnan (Hangkong gongcheng jinzhan)
During the flight test of a certain type of helicopter, there was an abnormal parking fault of the left engine in the air. The pilot landed safely according to the special situation handling method, ensuring the safety of the aircraft. After landing, a static inspection was conducted on the faulty engine and no abnormalities were found. Subsequently, the entire aircraft was powered on and ground driven to check that the left engine was working normally.After data interpretation and analysis, it was determined that the abnormal decrease in P3 pressure caused an abnormal decrease in the limit value of the oil to gas ratio, resulting in fuel limitation and engine shutdown. This article analyzes the single engine parking fault in the air, describes the special situation handling methods after single engine parking from the perspective of the flight test team, analyzes that there is movable metal surplus in the P3 pressure sensor of the helicopter, which causes a short circuit between the power supply of the conditioning circuit and the ground in short time during the flight of the helicopter, and causes the voltage in the electronic controller to be pulled down, causes P3 signal abnormal fall, and eventually leads to the helicopter in the air without warning abnormal single stop, and proposes improvement measures and suggestions, providing ideas for model design and special situation fault analysis.